PERJANJIAN TRIPS DAN BEBERAPA ISU STRATEGIS (TRIPS AGREEMENT AND SEVERAL STRATEGIC ISSUES) - Hakim, Fika (Indonesia Law Review, 2011)
Intellectual Property Rights is one of the most important aspects of foreign investment. Although intellectual property rights is a key element in the TRIPs Agreement, but this book does not discuss the specifics of Intellectual Property Rights (hereinafter referred to as IPR) itself. This book also addresses three other strategic issues in addition to IPR, which are transfer of technology, Traditional Knowledge and Genetic Resources Folklore (SGPTF), and TRIPS Plus. In addition, the book also discusses the relation between TRIPs and the developing countries, especially Indonesia, and also its relation to developed countries.